Characteristics of Elderly Patients with Sarcopenia at Geriatric Outpatient Clinic Dr. Hasan Sadikin General Hospital Period 2012–2014 - Sania Putri Darwita; Yuni S. Pratiwi; Lazuardhi Dwipa (Althea Medical Journal, 2018)
Background: Sarcopenia can lead to difficulty in physical activities, therefore, elderly cannot live independently. However, data on sarcopenia are not yet available in Dr. Hasan Sadikin General Hospital. This study was conducted to identify the frequency of occurrence and characteristics of elderly patients with sarcopenia.Methods: This study used descriptive method and was conducted from May to October 2014. Total sampling method was performed to medical records of elderly patients with sarcopenia at Geriatric Outpatient Clinic Dr. Hasan Sadikin General Hospital during the period 2012–2014. Variables observed were age, gender, body mass index (BMI), activities of daily living (ADL), timed up and go test (TUG), mini nutritional assessment (MNA), disease record, and medication record. Patients with sarcopenia were then grouped based on characteristics of age, gender, BMI, ADL, TUG, MNA, disease record, and medication record.Results: Out of 255 registered elderly patients, 22(8.63%) were with sarcopenia and one was excluded due to incomplete data. Sarcopenia was most prevalent in patients aged 80 years and older (15.38%), and commonly in men (57.1%). Most patients had hypertension history (66.6%), multiple comorbidities (61.9%), normal BMI (33.3%), normal ADL (85.7%), normal MNA (76.1%), and normal TUG scores (80.9%), and polypharmacy (52.3%) history.Conclusions: Sarcopenia is prevalent in men aged 80 years and older. Although sarcopenia patients have hypertension history, multiple comorbidities and history of polypharmacy, most patients live with normal daily activities and have good body mass index, however, quality of life of elderlies needs to be improved further.